Storage stability of Nile tilapia meat mechanically separated, washed, added with preservatives and frozen - Kirschnik, Peter Gaberz; Trindade, Marco Antonio; Gomide, Catarina Abdala; Moro, Maria Estela Gaglianone; Viegas, Elisabete Maria Macedo (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the influence of the washing process and of the addition of sodium erythorbate and sodium tripolyphosphate on the stability of mechanically separated meat (MSM), obtained from Nile tilapia (Oreochromis niloticus) filleting waste. Four treatments were evaluated, in triplicate: washed or nonwashed MSM, stored with or without the addition of preservatives, during 180 day storage at ‑18ºC. To evaluate stability, microbiological, nonprotein nitrogen, volatile basic nitrogen, lipid oxidation by Tbars index, pH value, and drip loss analyses were carried out. The washing process increased moisture content and decreased crude protein, fat, and ash contents in MSM, as well as the levels of nonprotein nitrogen, volatile basic nitrogen, and lipid oxidation after washing. During storage, no differences were detected for nonprotein nitrogen levels, pH values, and drip loss, but there was an increase in volatile basic nitrogen values. The washing process favors tilapia MSM stability, and the addition of sodium tripolyphosphate and erythorbate reduces lipid oxidation of the unwashed product.